Revisão sistemática dos equinoides (Echinodermata) na Formação Jandaíra (Cretáceo) Bacia Potiguar, Nordeste do Brasil - Oliveira, Josevânia de (2013)
The Cretaceous was a time of many changes on the earth s surface that contributed to develop a rich diversity of organisms. The Potiguar Basin is situated on the northeast coast of Brazil and it occupies the northern part of Rio Grande do Norte and Ceará states. It is a basin formed by the Cretaceous rift that occurred during the installation of the South Atlantic Ocean. The representatives of the Echinoidea class are abundantly present in the Jandaíra Formation, so that it s possible to find extensive banks composed of their shells. This study aimed to do the systematic review of the echinoid species from the Jandaíra Formation, Potiguar Basin. In this study we analyzed, described and illustrated 223 specimens of echinoids from six locations in Jandaíra Formation. The specimens were obtained from samples collected in 2003 and 2011, and deposited in the collection of the Phoenix Paleontological Foundation (FPH). Were identified and reviewed seven echinoids species: three regular echinoids, Rosadosoma riograndensis (Maury, 1925), Phymosoma major Coquand, 1862 and Goniopygus durandi (Perón & Gauthier, 1881), and four irregular ones: Petalobrissus setifensis (Cotteau, 1866), Petalobrissus cubensis (Weisbord, 1934), Mecaster fourneli (Deshayes in Agassiz & Desor, 1847) and Mecaster texanum (Roemer, 1852). The regular echinoids biometric data showed that the carapace diameter significantly influences the height of the carapace and the peristome diameter. The specimens of regular echinoids were in different ontogenetic stages, as well as the irregular ones, although the morphological characteristics were similar regardless of their stages. The specimens Petalobrissus setifensis and P. cubensis were compared among themselves and with the ones registered for other regions, as well as the M. fourneli and M. texanum specimens. Regarding to the paleobiogeographic quinoids distribution in Jandaíra Formation, it was observed that, on the locations here studied, the species of irregular echinoids exhibited a wider geographic distribution when compared to the regular species. The species of regular echinoids have a more frequent occurrence from the Turonian to the Santonian and the irregular species from the Turonian to the Campanian of the Jandaíra Formation. Our study was of great importance, since it contributed to the systematic review of the echinoids species and the in clarifying the possible junior synonyms and the morphological changes exhibited by the echinoids specimens in different ontogenetic stages. This study was of great importance, since it contributed in the systematic description and the morphological variations exhibited at the echinoids species in different ontogenetic stages.